Digital Words, Real Results? Testing The “English Vocabulary” App In A High School Setting - Nasrifah; Ul Haq, Muhammad Zia; Sastrawati, Ika (Journal of Computer Interaction in Education, 2025)
This study examines the effectiveness of the "English Vocabulary" mobile application in enhancing vocabulary mastery among students at SMKN 1 Polewali. In response to the increasing integration of technology in language education, this research addresses the urgent need to evaluate digital tools for vocabulary acquisition. Employing a pre-experimental quantitative design, data were collected through pre- and post-tests administered before and after treatment using the application. The findings revealed a substantial increase in student performance, with mean scores rising from 43.33 to 74.81. Statistical analyses confirmed normal data distribution and homogeneity, and the paired sample t-test indicated a significant improvement (Sig. 2-tailed = 0.000 < 0.05). These results confirm the application’s positive impact on vocabulary development. The study contributes to the field by providing empirical evidence supporting the effectiveness of mobile-assisted vocabulary learning and recommends the integration of such applications in formal education to enhance learners' lexical competence.